Optimal shielding thickness for galactic cosmic ray environments. (February 2017) - Slaba, Tony C.; Bahadori, Amir A.; Reddell, Brandon D.; Singleterry, Robert C.; Clowdsley, Martha S.; Blattnig, Steve R.
Abstract: Models have been extensively used in the past to evaluate and develop material optimization and shield design strategies for astronauts exposed to galactic cosmic rays (GCR) on long duration missions. A persistent conclusion from many of these studies was that passive shielding strategies are inefficient at reducing astronaut exposure levels and the mass required to significantly reduce the exposure is infeasible, given launch and associated cost constraints. An important assumption of this paradigm is that adding shielding mass does not substantially increase astronaut exposure levels. Recent studies with HZETRN have suggested, however, that dose equivalent values actually increase beyond ∼20 g/cm 2 of aluminum shielding, primarily as a result of neutron build-up in the shielding geometry. In this work, various Monte Carlo (MC) codes and 3DHZETRN are evaluated in slab geometry to verify the existence of a local minimum in the dose equivalent versus aluminum thickness curve near 20 g/cm 2 . The same codes are also evaluated in polyethylene shielding, where no local minimum is observed, to provide a comparison between the two materials. Results are presented so that the physical interactions driving build-up in dose equivalent values can be easily observed and explained. Variation of transport model results for light ions (Z ≤ 2) and neutron-induced target fragments, which contribute significantly to dose equivalent for thick shielding, is also highlighted and indicates that significant uncertainties are still present in the models for some particles. The 3DHZETRN code is then further evaluated over a range of related slab geometries to draw closer connection to more realistic scenarios. Future work will examine these related geometries in more detail.